1998
DOI: 10.1111/1468-5957.00196
|View full text |Cite
|
Sign up to set email alerts
|

Robust Estimation of Beta Coefficients: Evidence from a Small Stock Market

Abstract: In this paper we demonstrate that robust estimators improve the reliability of estimates of beta coefficients on small, thinly traded stock markets. We outline several different types of robust and bounded influence regression estimators and assess them using a jackknife methodology on data from the Johannesburg Stock Exchange. The empirical evidence confirms the hypothesis that robust estimators are more efficient than least squares estimators and indicates that least squares estimators may over-estimate syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
5
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
6
5
0
1
Order By: Relevance
“…The empirical results showed that in most cases, the Gini estimator was more efficient and consistent than the OLS estimator. This finding was consistent with other studies ( Chan and Lakonishok, 1992 ; Bowie and Bradfield, 1998 ). However, this research employed only one data type, horizon data, and criterion in comparison.…”
Section: Literature Reviewsupporting
confidence: 94%
See 2 more Smart Citations
“…The empirical results showed that in most cases, the Gini estimator was more efficient and consistent than the OLS estimator. This finding was consistent with other studies ( Chan and Lakonishok, 1992 ; Bowie and Bradfield, 1998 ). However, this research employed only one data type, horizon data, and criterion in comparison.…”
Section: Literature Reviewsupporting
confidence: 94%
“…This TT method worked best in the case of daily periodicity because it produced the smallest beta standard deviation estimates compared with weekly and monthly periodicity. This finding was consistent with other studies (e.g., Chan and Lakonishok, 1992 ; Bowie and Bradfield, 1998 ; Shalit and Yitzhaki, 2002 ). However, this research employed only one horizon data and criterion in comparison.…”
Section: Literature Reviewsupporting
confidence: 94%
See 1 more Smart Citation
“…aside the performance of the methods with respect to alpha estimation. Bowie and Bradfield (1998) extended the work of Chan and Lakonishok (1992) by assessing the relative performance of a wider range of robust estimators when applied for beta estimation of securities listed on the Johannesburg Stock Exchange. Their results, based on jackknife measures of efficiency, indicate that robust methods are less sensitive than OLS to model misspecification -such as extreme excess market returns -, and that the superior efficiency of the robust estimators was caused by non-normality in the distribution of residuals.…”
Section: Robust Estimation Of Asset Pricing Modelsmentioning
confidence: 99%
“…Luego, un análisis comparativo de los diferentes estimadores robustos fue introducido por Bowie & Bradfield (1998), concluyendo que el estimador de influencia limitada de la familia de estimadores M es el que presenta una mayor eficiencia en la estimación, en comparación con el estimador MCO. Los autores también indican que las diferencias sistemáticas entre MCO y los estimadores robustos, motivan a los investigadores a profundizar en la relación que existe entre el retorno de las acciones y el retorno del mercado cuando se presentan condiciones extremas derivadas de la baja liquidez de algunos activos, tal como se presenta en mercados financieros de poca profundidad y desarrollo.…”
Section: Relevancia De La Estadística Robusta En Finanzasunclassified